Use of Three-Dimensional Printing in Modelling an Anatomical Structure with a High Computed Tomography Attenuation Value: A Feasibility Study - Kariyawasam, L.N.; Ng, Curtise; Sun, Zhonghua; Kealley, C.S. (American Scientific Publishers, 2021)
Introduction